PRAKTEK PENYIMPANAN BENIH PADI LOKAL DAN NASIONAL DI KEPULAUAN BANGKA - wahyuni, Winda wahyuni; Kartika, Kartika (Enviagro: Jurnal Pertanian dan Lingkungan, 2024)
Rice production in the Bangka Islands often fluctuates, which is thought to be because the quality of the seeds used in the Bangka Islands is still very low. One of the efforts that can be made to maintain the quality of seeds during storage is temperature and humidity. This experiment aims to determine the best storage of local red rice, varieties IR 64 and Inpari 42 in the Bangka Islands. This experiment was carried out at the Seed Technology Laboratory, Agrotechnology Study Program, Faculty of Agriculture, Fisheries and Maritime Affairs, Bangka Belitung University. The experiment was carried out using a completely randomized design where the storage temperature was the factor, namely room temperature and refrigerator temperature and was repeated 4 times. The experimental results showed that local Red Ampai rice seeds, and IR64 and Inpari42 seeds stored at room temperature had better viability and vigor values than refrigerator temperatures. The type of packaging in the form of plastic also influences the storage of rice seeds. Keywords : local accession, seed quality, storage period, temperature